1985
DOI: 10.1016/0020-7292(85)90008-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma arginine vasopressin response to water load during labor

Abstract: To find out whether plasma vasopressin (PAVP) response to a water load during pregnancy is inappropriately high, as had been speculated, we measured PAVP by radioimmunoassay in 30 women at the time of delivery. Ten women had received infusion of aqueous glucose solution during labor for hydration (GW group); another ten received infusion of glucose solution as a vehicle for oxytocin (OT group), and ten women did not receive any intrapartum intravenous fluid therapy (controls). Serum sodium and osmolality were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Typically, this may occur postoperatively, but during labour stimuli for vasopressin release are abundant. Labour itself is, however, not a situation causing inappropriate vasopressin secretion 22. The women in our study received fluid volumes well below their predicted maximum capacity of renal excretion at rest; therefore, the development of hyponatraemia indicates increased vasopressin activity during labour.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Typically, this may occur postoperatively, but during labour stimuli for vasopressin release are abundant. Labour itself is, however, not a situation causing inappropriate vasopressin secretion 22. The women in our study received fluid volumes well below their predicted maximum capacity of renal excretion at rest; therefore, the development of hyponatraemia indicates increased vasopressin activity during labour.…”
Section: Discussionmentioning
confidence: 76%
“…Labour itself is, however, not a situation causing inappropriate vasopressin secretion. 22 The women in our study received fluid volumes well below their predicted maximum capacity of renal excretion at rest; therefore, the development of hyponatraemia indicates increased vasopressin activity during labour. Our results indicate that fluid volume is the major determinant of hyponatraemia, but the antidiuretic effects of endogenous vasopressin and oxytocin administration increase the susceptibility of women to develop hyponatraemia during labour.…”
Section: Oralfluidsmentioning
confidence: 81%
“…Furthermore, research demonstrated a significant decrease in plasma vasopressin levels at 15 and 45 min of immersion to the chest in parturients at term gestation (Benfield et al, 2010). Similarly, vasopressin levels were significantly lower in parturients who received an infusion of a glucose solution compared to those who only sipped oral fluids (Singhi & Parshad, 1985). Conversely, vasopressin levels were elevated in women with primary dysmenorrhea (Stromberg, Åkerlund, Forsling, Granström, & Kindahl, 1984).…”
mentioning
confidence: 99%